Feedback Effectiveness Attributional Modification Schunk Model for Improvement of Academic Self-Efficacy Primary School Students in Math Lesson - Asrori Asrori (JETL (Journal of Education, Teaching and Learning), 2017)
This experimental study examines the effect of Schunk Model's attributional feedback to improve academic self-efficacy of elementary school underachievers and low achievers in mathematics. The hypothesis that student who receives an attributional feedback, either oral or written, both get higher scores on self-efficacy and mathematics achievement than control group was Examined. The elementary students' grade III and IV Whose mathematics Reviews their achievements were below average grade was Involved as a research subject. With the random procedure, the subjects were assigned to one of three groups: (1) oral attributional feedback, (2) written attributional feedback, (3) reinforcement feedback and (4) no treatment. Profile analysis indicates that oral feedback and reinforcement attributional more effective to increase of mathematics self-efficacy and students' achievement than written. Analysis of variance with Least Significant Difference indicates that students who receive either oral or written feedback attributional got higher scores on mathematics self-efficacy and achievement than the control group. Furthermore, factorial design analysis indicates that attributional feedback, either oral or written, was more effective than low achievers to underachievers.